On novel security systems based on the 2-cyclic refined integers and the foundations of 2-cyclic refined number theory - Mohammad Abobala; Hasan Sankari; Mohamed Zeina (Journal of Fuzzy Extension and Applications)
Integers play a basic role in the structures of asymmetric crypto-algorithms. Many famous public key crypto-schemes use the basics of number theory to share keys and decrypt and encrypt messages and multimedia. As a novel trend in the world of cryptography, non-classical integer systems, such as neutrosophic or plithogenic integers, are used for encryption and decryption. The objective of this paper is to provide the basic foundations of 2-cyclic refined number theory and linear Diophantine equations in two variables by building suitable algebraic isomorphism between the 2-cyclic refined integer ring and a subring of the direct product of Z with itself three times. Also, this work presents two novel crypto schemes for the encryption and decryption of data and information based on the algebraic properties of 2-cyclic refined integers, where improved versions of the El-Gamal crypto-scheme and RSA algorithm will be established through the view of the algebra and number theory of 2-cyclic refined integers. On the other hand, we illustrate some examples and tables to show the validity and complexity of the novel algorithms.